2003
DOI: 10.1074/jbc.m302671200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of p53-dependent Activation of the Human Proliferating Cell Nuclear Antigen Gene in Chromatin by Ionizing Radiation

Abstract: A human fibroblast cell line with conditional p53 expression displayed a p53-dependent increase in both the protein and mRNA levels of proliferating cell nuclear antigen (PCNA) after exposure to ionizing radiation (IR). The combination of p53 induction and IR cooperated to activate a transiently expressed human PCNA promoter-reporter gene via a p53-responsive element. Chromatin immunoprecipitation assays with antibodies specific for p53 or p300/CREB-binding protein revealed specific p53-dependent enrichment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…S3B). A similar pattern (data not shown) of p53 and ER␣ binding was observed on the p53-response element of the PCNA gene, another transcriptional target of p53 (20). Immunoblotting analysis showed that the ER␣ expression was unaffected, and the p53 level, as expected, was increased by irradiation (Fig.…”
Section: Resultssupporting
confidence: 57%
“…S3B). A similar pattern (data not shown) of p53 and ER␣ binding was observed on the p53-response element of the PCNA gene, another transcriptional target of p53 (20). Immunoblotting analysis showed that the ER␣ expression was unaffected, and the p53 level, as expected, was increased by irradiation (Fig.…”
Section: Resultssupporting
confidence: 57%
“…As expected, the ChIP-chip screen identified some known p53 target genes: glutathione peroxidase 1 (GPX1) (74), PCNA (72), jagged 2 (JAG2) (70), and c-myc (MYC) (30). GPX1, PCNA, and MYC have p53 response elements that have been described previously (72,74,78). The promoters for both GPX1 and PCNA have p53REs within the CGIs identified from the array.…”
Section: Resultsmentioning
confidence: 88%
“…The promoters for both GPX1 and PCNA have p53REs within the CGIs identified from the array. Interestingly, three CGIs have been mapped to the PCNA locus (6 kb upstream, 500 bp upstream, and 6 kb downstream) (28), but only one was enriched for p53 binding (2.11-fold enrichment) and contains a previously reported p53RE at Ϫ278 bp (72). The MYC locus has several predicted p53REs located throughout the exon and intron structure of the human gene (78).…”
Section: Resultsmentioning
confidence: 99%
“…We observed dose-dependent increases in PCNA expression with increasing CT dose (mGy cm) and dose-dependent increases in TP53 and FLT3LG expression with increasing effective CT dose (mSv), which are in accordance with in vitro studies reporting increases in gene expression or protein concentrations after IR exposure. 45,46 Next, we examined correlations between the gene expression levels and IR history. In our subjects, regression analyses revealed that previous exposure to IR (either through prior CT scans or X-rays) was dose dependently related to MDM2 levels.…”
Section: Discussionmentioning
confidence: 99%